Functional characterisation of cardiac progenitors from patients with ischaemic heart disease - Zhang, H (2013)
Ischaemic heart disease (IHD) is the leading cause of death worldwide. Currently, even optimal medical therapies do not attenuate deterioration of the left ventricular (LV) function completely. Stem cell therapies, and recently cardiac stem cell therapies, have emerged as potential novel treatments for IHD. However, clinical evidence from randomised controlled studies has shown mixed results. Thus understanding what patient-related factors may affect the therapeutic performance of the cells may help improving treatment outcomes. The studies described in this thesis aim to understand how cardiac progenitor cells (CPCs) can re-vascularise ischaemic myocardium and promote functional repair of the heart. Resident CPCs were isolated and expanded from the right atrial appendage of 68 patients following the ‘cardiosphere’ method (cardiosphere-derived cells or CDCs). They resemble mesenchymal progenitors as they lack the expression of endothelial and haematopoietic cell surface markers but express mesenchymal progenitor cell markers (e.g. CD105, CD90). Cell function was evaluated by support of angiogenesis, mesenchymal lineage differentiation potential in vitro, and improvement in heart function in vivo. Notably in vitro, CDC from different patients differed in their angiogenic supportive and differentiation potentials. In a rodent model of myocardial infarction (MI), transplantation of CDC reduced infarct size significantly (p<0.05). However, only those CDCs with a robust pro-angiogenic ability in vitro improved vessel density and heart systolic function (p<0.05) in vivo. A multiple regression model, which accounted for 51% of the variability observed, identified New York Heart Association (NYHA) class, smoking, hypertension, type of ischaemic disease and diseased vessel as independent predictors of angiogenesis. In addition, gene expression analyses revealed that differential gene expression of several extracellular matrix components (e.g. CUX1, COL1A2, BMP1 genes and microRNA-29b) could explain the differences observed in CDC’s vascular supportive function. In summary, this is the first description of variability in the pro-angiogenic and differentiation potential of CDCs and its correlation with their therapeutic potential. This study indicates that patient stratification may need to be included in the design of future trials to improve the efficacy of cell-based therapies.